Cultural psychology: A once and future discipline - Cole, Michael (Cambridge, Massachusetts The Belknap Press of Harvard University Press, 1996)
The distinguished psychologist Michael Cole, known for his pioneering work in literacy, cognition, and human development, offers a multifaceted account of what cultural psychology is, what it has been, and what it can be. A rare synthesis of the theory and empirical work shaping the field, this book will become a major foundation for the emerging discipline.